The Modified Yale Food Addiction Scale 2.0: Validation Among Non-Clinical and Clinical French-Speaking Samples and Comparison With the Full Yale Food Addiction Scale 2.0 - Brunault, Paul; Berthoz, Sylvie; Gearhardt, Ashley N.; Gierski, Fabien; Kaladjian, Arthur; Bertin, Eric; Tchernof, André; Biertho, Laurent; de Luca, Arnaud; Hankard, Régis; Courtois, Robert; Ballon, Nicolas; et al. (Frontiers in Psychiatry, 2020)
Objectives: The modified Yale Food Addiction Scale 2.0 (mYFAS 2.0) was designed to assess food addiction using a shorter version than the YFAS 2.0. We lack data about the psychometric properties of the mYFAS 2.0 in patients with obesity, as well as studies comparing the psychometric properties of the mYFAS 2.0 versus the full YFAS 2.0. This study aimed to validate the French-language mYFAS 2.0 in a non-clinical population (study 1, n=250), to determine the yet unknown psychometric properties of this scale in patients with obesity (study 2, n=345), and to compare the full YFAS 2.0 and the mYFAS 2.0 in terms of food addiction (FA) prevalence and symptoms detection in both populations. Method: Study 1 included 250 non-clinical individuals (non-underweight and non-obese persons screened negative for eating disorders). Study 2 included 345 bariatric surgery candidates recruited in three centers (Québec, Canada; Reims and Tours, France). The mYFAS 2.0 structure was investigated using confirmatory (study 1) and exploratory (study 2) factorial analyses. Convergent validity was tested using the full YFAS 2.0, the Binge Eating Scale (both studies), the revised 18-item Three Factor Eating Questionnaire (study 1), the Beck Depression Inventory (study 2) and the body mass index (BMI; both studies). Results: The mYFAS 2.0 was unidimensional, and had adequate (study 1: KR-20=.78) and acceptable (study 2: KR-20=.73) internal consistency. In study 1, the mYFAS 2.0 had good convergent validity with the YFAS 2.0, BMI, binge eating, cognitive restraint, uncontrolled eating and emotional eating; in study 2, the mYFAS 2.0 had good convergent validity with the YFAS 2.0, binge eating, depression, but not BMI. Participants endorsed fewer symptoms with the mYFAS 2.0 than with the YFAS 2.0; FA prevalences were similar between questionnaires in the non-clinical, but not in the clinical sample. A FA ‘diagnosis’ and risk of binge eating disorder were associated, but did not completely overlap. Conclusions: The mYFAS 2.0 has close psychometric properties to the YFAS 2.0 in non-clinical and clinical samples. However, the use of the mYFAS 2.0 in bariatric surgery candidates might lead to a significant underestimation of FA prevalence and number of FA symptoms.